300-GHz-band wireless communication using a low phase noise photonic source. Issue 7 (7th September 2020) - Yi, L.; Iwamoto, K.; Yamamoto, T.; Ayano, F.; Rolland, A.; Kuse, N.; Fermann, M.; Li, Y.; Nagatsuma, T.
Abstract: The implementation of advanced multi-level modulation schemes such as quadrature phase-shift keying (QPSK) in contrast to the conventional on–off keying is crucial to further boost the terahertz (THz) communications speed. Thereby, carrier phase noise reduction in the THz range is one of the key goals that need to be urgently achieved. In this paper, the photonic-based THz sources and the phase noise problem are briefly summarized. Then, a low phase-noise photonic source based on the stimulated Brillouin scattering (SBS) optical fiber cavity is first applied for a 300-GHz-band QPSK wireless communication link. The highest data rate at forward-error-correction limited condition was 15 Gbaud utilizing the SBS-based photonic source with a small transmit power of ~ −36 dBm. Its transmission characteristics are evaluated and compared with the conventional optical frequency comb generator (OFCG)-based source at 5 Gbaud. The proposed SBS-based photonic source has been proven to offer better performances than the OFCG-based source with respect to the phase noise, optical carrier to noise ratio, and bit error rate in communications.